Essentials of contemporary business statistics - Williams. A. Thomas 2007 (USA Thomson corporation, 2007)
"In this ninth edition of Essentials of Contemporary Management, we continue to focus on providing the most up-to-date account of the changes taking place in the world of management and management practices while maintaining our emphasis on making our text relevant and interesting to students. And we know from feedback from instructors and students that the text does engage them. Our increased focus on the challenges and opportunities facing businesses large and small and integrated timely examples bring management issues to life for students"--
Revised edition.
Ages 18+
Keywords: Management